2018
DOI: 10.1016/s2352-4642(18)30026-9
|View full text |Cite
|
Sign up to set email alerts
|

MRI and laboratory features and the performance of international criteria in the diagnosis of multiple sclerosis in children and adolescents: a prospective cohort study

Abstract: The Multiple Sclerosis Scientific Research Foundation and The Children's Hospital of Philadelphia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
0
18

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(93 citation statements)
references
References 25 publications
2
73
0
18
Order By: Relevance
“…In particular, future studies should aim to quantify the effect of seropositive-related demyelination on age-expected brain growth and white matter maturation, both of which are negatively affected in MS, 19,[31][32][33] and on cognitive performance. All of this information is essential to better inform the risk-to-benefit ratio of long-term immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, future studies should aim to quantify the effect of seropositive-related demyelination on age-expected brain growth and white matter maturation, both of which are negatively affected in MS, 19,[31][32][33] and on cognitive performance. All of this information is essential to better inform the risk-to-benefit ratio of long-term immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…Research MRI scans included axial and sagittal T2-weighted images, fluid-attenuated inversion recovery images, T1weighted images, and T1-weighted images after administration of gadolinium. Scans acquired within 45 days of clinical presentation were analyzed by applying a standardized scoring tool 18 modified to include additional MRI variables 19 and blinded to MOG status and to clinical outcome.…”
Section: Mri Analysismentioning
confidence: 99%
“…The Canadian Paediatric Demyelinating Disease network has shown that the 2017 McDonald criteria for the diagnosis of MS, when applied at the time of onset, performed well in identifying children and young people with MS. The criteria were also checked in children with acute disseminated encephalomyelitis (ADEM) and myelin oligodendrocyte antibody positive 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, we consider relevant to validate the 2017 criteria in other regions/countries as well as in different age groups, such as children ≤10 years of age, adolescents or patients with lateonset MS. For example, a study assessing the criteria in Korean patients demonstrated similar diagnostic properties as a Dutch study [16,17]. Another study in children aged 0.46-17.87 years showed the 2017 criteria performed well across the studied age span, with presence of OB improving the diagnostic accuracy [18]. These results suggest that if the McDonald criteria are applied to patients presenting with typical symptoms suggestive of MS, they should be valid in any population, always keeping in mind that the diagnosis of MS should be done only when other diseases have been ruled out.…”
Section: To Include or Not To Include Oligoclonal Bands?mentioning
confidence: 76%